2022
DOI: 10.1177/1420326x211048537
|View full text |Cite
|
Sign up to set email alerts
|

How community medical facilities can promote resilient community constructions under the background of pandemics

Abstract: Nowadays, urban and community resilience have become the core issues of urban theoretical research and construction practices. While there are many studies on climate change, natural hazards and environmental pollution, relatively less attention has been paid to public and human health. However, the current COVID-19 pandemic, which is a major global public health crisis, is posing severe challenges to the resilience of cities and communities in the context of high-mobility, high-density and high-intensity, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…There has been an upswing in health-services research efforts that search for easily-attainable and observable measures to enforce health system’s resilience by adapting theories and models of resilience to the peculiarities of healthcare [ 1 ]. Although socioeconomic shocks affect health systems on a macro level, the effects materialize in place-specific consequences on primary care, accounting for the notion of regional-care resilience [ 21 ]. So far, health services research has neglected further investigation of regional resilience of gynecological and obstetric care in light of multiple socioeconomic shocks.…”
Section: Discussionmentioning
confidence: 99%
“…There has been an upswing in health-services research efforts that search for easily-attainable and observable measures to enforce health system’s resilience by adapting theories and models of resilience to the peculiarities of healthcare [ 1 ]. Although socioeconomic shocks affect health systems on a macro level, the effects materialize in place-specific consequences on primary care, accounting for the notion of regional-care resilience [ 21 ]. So far, health services research has neglected further investigation of regional resilience of gynecological and obstetric care in light of multiple socioeconomic shocks.…”
Section: Discussionmentioning
confidence: 99%
“…Government departments should establish emergency response plans for major public health emergencies, such as setting up temporary hospitals in areas where medical resources are scarce and setting up designated hospitals in their vicinity to safeguard the public’s demand for medical treatment and alleviate negative public sentiment. In addition, community medical facilities play a vital role in the control of the COVID-19 epidemic [ 93 ], and should respond to the advocacy of “Building a 15 min Community Life Circle” [ 94 ], strengthen the construction of primary healthcare system, improve the level of medical services in community hospitals, and convenience residents by enabling access to medical services closer to home.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Many studies have therefore suggested that the community environment should be improved and resilient communities should be built. 21,22 In older communities, narrow building spaces and unreasonable building layouts could more easily lead to the widespread existence of vortex zones and wind-free zones. In the vortex zone or in the wind-free zone in the residential area, viral contaminants and air pollutants could be highly susceptible to accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…1820 Many studies have therefore suggested that the community environment should be improved and resilient communities should be built. 21,22…”
Section: Introductionmentioning
confidence: 99%